Examining several factors that influence corporate social responsibility disclosure - Gaffar, Samsu; Akal, Andi Tenri Uleng; Sarnawiah, Sarnawiah; Nur, Kherayani; Rahmawati, A.; Nurwana, Nurwana (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study aims to analyze the impact of Company Size, Profitability, and Foreign Ownership on Corporate Social Responsibility (CSR) Disclosure in mining companies listed on the Stock Exchange. Specifically, it aims to determine whether these factors significantly influence CSR disclosure. This study utilizes secondary data from the financial statements of mining companies listed on the IDX. Multiple linear regression analysis assesses the relationship between Company Size, Profitability, Foreign Ownership, and CSR Disclosure. The analysis aims to establish these factors' individual and combined effects on CSR disclosure in the mining industry. This study's findings indicate that the company's size positively influences CSR disclosure. Larger companies tend to exhibit higher levels of CSR disclosure. Additionally, profitability positively and significantly impacts CSR disclosure, suggesting that more profitable mining companies tend to disclose more about their social responsibility initiatives. The results also demonstrate that the ownership of foreign shares owned by the company positively influences CSR disclosure. As the ownership of foreign shares increases, the level of CSR disclosure also increases. Furthermore, the study concludes that when considering Company Size, Profitability, and Foreign Ownership, they collectively positively and significantly affect corporate social responsibility. This study contributes to the existing literature by examining the impact of Company Size, Profitability, and Foreign Ownership on CSR Disclosure, specifically in the mining sector. The findings provide insights into the factors that affect the extent of CSR disclosure, which can help mining companies and stakeholders enhance their understanding and awareness of social responsibility practices within the industry.